From Theory to Practice: Exploring Strategic IS Alignment in the Textile Sector of Meknes, Morocco - R.Achchak; C.Houmami; A. Bouwdad; Y.Lafraxo (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to realize the importance of strategic alignment between IS and organizational strategy on enabling business performance. The positive association of IS alignment with enhanced efficiency, cost minimization, and competitive advantage has been corroborated by a systematic review of extant literature. Yet this is complex, yet strategic alignment guarantees that IS technology align with organizational objectives to allow the businesses to maneuver the competitive and dynamic markets. The empirical case study was undertaken in SEFITA, a textile organization based in Meknes Morocco that adopts IS to enhance its operations, to complement the literature. We find that strategic IS alignment also increases the operational efficiency and competitive positioning of SEFITA, confirming the theoretical foundations presented in the literature According to our research, in order to attain long-term performance improvements, organizations need to incorporate IS planning into their strategic frameworks and put in place ongoing alignment processes.